Alat Pemadam Api Terarah Dalam Ruangan Berdasarkan Warna HSV Berbasis Raspberry Pi - Wahyu Hari Suwito; Hurriyatul Fitriyah; Gembong Edhi Setyawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
A fire disaster is a catastrophic event that causes a fire, which can cause harm both from property, and casualties. Therefore, a system is needed to minimize the occurrence of fires in the house, in this study will provide a more effective solution in detecting and extinguishing fires to prevent fires. By utilizing image processing on the camera, then pump dc water as a water sprayer. The system uses the Raspberry Pi computer as a data processing center, Logitech c170 camera as the input data provider that processes the image, then there is a Servo mg995 as a water hose guide, and a DC 5v Mini Water Pump as a water pump. Taking Logitech c170 camera images will later be converted into HSV Color Space, selecting Upper & Lower HSV levels. Then mark the fire with a red dot and give a circle using MinEnclosingCircle. Then the system classifies hotspots in several categories of fire position positions. Next the system will send data on the Servo mg995 which will move towards the location of the hotspot, turning on the DC 5v Mini Water Pump as a water sprayer. The level of accuracy of the system in recognizing fire points is 88.9%. While testing in determining the location of fire was 92.3%. And the last is a complete fire extinguishing test of 100%.